KUALITAS PELAYANAN PASPOR DI KANTOR IMIGRASI KELAS I TEMPAT PEMERIKSAAN IMIGRASI (TPI) SURAKARTA TAHUN 2022 - Andhika Rahmayana Joenoes; Joko Pramono; Aris Tri Haryanto (JI@P, 2023)
The passport application process is easier, faster, with minimal data errors, andfriendly for the elderly and disabled at the Surakarta Immigration Office.However, in its implementation there are problems, including: 1) Not yet optimalinnovation of information technology-based public services. 2) Minimum numberof competent human resources in the field of information technology. 3) Thefacilities and infrastructure for supporting information technology-based servicesare not yet optimal. The purpose of this study was to analyze and determine thequality of passport services at the Class I Immigration Office at the SurakartaImmigration Checkpoint. This study uses a descriptive method with a qualitativeapproach. Research informants using purposive sampling technique. Datacollection techniques using interviews, and documentation. The data analysistechnique used is interactive analysis which consists of data reduction, datapresentation and conclusion drawing. The results showed that the service qualityof Surakarta immigration office employees from the dimension of tangibles hasnot fully provided satisfaction for community, including not optimal facilities andinfrastructure supporting information technology-based services and lack ofparking lots. From the dimension of reliability has not been seen well because ofthe minimum number of competent human resources in the field of InformationTechnology. In terms of responsiveness, has not shown optimal service quality.The dimension of assurance, shows the services that have been carried out inaccordance with the applicable provisions, but in terms of providing guarantees,the time for granting passports is sometimes not on time. From the dimension ofempathy shows a good quality of Service. In performing their duties, employeesserve well to passport applicants.Keywords: Tangibles, Reliability, Responsiveness, Assurance and Empathy